An Exploration of Changes in British Welfare Social Policy in the First Half of the Twentieth Century through Bourdieu's Theory of Field and Habitus - Zhao, Zeming (Transactions on Social Science, Education and Humanities Research, 2024)
The question of how to transcend the dichotomy between subjectivity and objectivity is a central one in contemporary sociological theory. Bourdieu advocates habitus as a cognitive framework that embodies an individual's practical understanding of society. Such practices consist of structures and habits, and social behaviour is not directly determined by structures, but is indirectly influenced by habitus as an 'embodied mode'. Habits, as 'opportunities for the subject', act as constraints on the formation of structures and contribute to their reproduction.  The welfare policy of Britain has experienced the transformation from solving the problem of the poor with a single welfare policy of relief law to the establishment of national economic law, which is continuously amended according to the native welfare policy habitus, thus affecting the welfare policy field and realising the two-way constraints of the field and habitus.